Performance of fiber-based QAM/FSO systems in turbulence with anisotropic tilt angle and random angular jitter - Chao Zhai; Zhenyuan Xue (Results in Engineering)
Recent experiments have demonstrated that the anisotropic property of turbulence cells is inherently present, and the long axis of turbulence cell possibly is not level with the ground but has an anisotropic tilt angle with it. Free-space optical (FSO) communication system based on fiber coupling can easily connect to terrestrial fiber network, thereby enabling the high-speed real-time space-ground integrated network, while random angular jitter has a substantial influence on fiber-coupling efficiency. However, the existing literature about the bit error rate (BER) performance of fiber-based FSO communication systems has been confined exclusively to the isotropic Kolmogorov and non-Kolmogorov turbulence models. To better align with realistic turbulence and practical application, we developed the expressions for probability density function (PDF) of fiber-coupling efficiency and BER of fiber-based quadrature amplitude modulation (QAM) FSO communication systems in the weak anisotropic non-Kolmogorov (ANK) horizontal link with anisotropic tilt angle and random angular jitter, for the first time. The results show that with the growing of anisotropic tilt angle γ, the average BER first decays and then increases, and the variation trend of BER is symmetrical about the straight-line γ = 90∘. The better BER performance of fiber-based QAM/FSO systems can be achieved by selecting lower QAM scheme, reducing random angular jitter, and optimizing focal length and receiver diameter. Our research can help understand the impacts of anisotropic tilt angle and random angular jitter on BER performance and benefit the design improvement of fiber-based FSO communication systems.